Development of an Arabic vocabulary selection model for lower secondary students using the Fuzzy Delphi method - Ab.Rahim, Rosyawati; Ismail, Taufik; Abu Bakar, Radhwa; Mustapha, Ramlan (e-International Publishing House Ltd., 2025)
The purpose of this project is to utilise the Fuzzy Delphi technique to develop an Arabic vocabulary selection model for Malaysian lower secondary students. The researcher chose five Arabic and educational specialists to assess important vocabulary selection factors. The experts identified five primary domains: instructional value, curriculum relevance, contextual suitability, frequency of use, and challenge level. Every Fuzzy Delphi criterion was met by the model, including the α-cut score (≥ 3.5), agreement (≥ 75%), and threshold value (d < 0.2). This concept can inform the development of more effective Arabic teaching resources.